The Effect of Music Therapy on Anxiety Levels in General Surgery Preoperative Patients: A Systematic Review - Madia Yuni Ardani; Sidik Awaludin (Indonesian Journal of Global Health Research, 2025)
Anxiety is a condition commonly experienced on the eve of surgery and has the potential to impact the condition and outcome of surgery negatively. Management strategies include pharmacological and non-pharmacological approaches, such as music therapy. Music The aim is to be a complementary alternative to pharmacological treatments to reduce patient anxiety. This systematic review analyzes nonpharmacological therapies used in the application of music therapy to general surgery patients with anxiety at the preoperative stage. The method uses articles published from 2014-2024 sourced from Science Direct, Pubmed, Cochrane Library, and Google Scholar databases. Article assessment was carried out using instruments from the Joana Briggs Institute. The result is based on seven articles that have been reviewed related to music therapy management to minimize anxiety scores owned by patients before undergoing surgical operations at the preoperative stage. Some articles explain that duration, type of music selection (natural sound), Turkish classical music, classical music from the West, jazz music, and religious music can reduce anxiety scores, maintain hemodynamic status, and maintain normal cortisol levels. In conclusion, music therapy is recommended as a nonpharmacologic method for anxiety management in preoperative patients.